Analisis Frasa dalam Kisah Sejarah pada Buku Ilmu Pengetahuan Sosial Kelas X Kurikulum Merdeka - Naazil Maharani An Nuur; Arfiatun Astia Ningrum; Darojatin Mansuriniati; Benedikta Agusta Kandam; Asep Purwo Yudi Utomo; Ristiyani Ristiyani (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
This study focuses on the analysis of phrases contained in the text of historical stories in class X textbooks of Social Sciences in the independence curriculum. This study uses a qualitative descriptive method and data collection techniques used are listening techniques, observation techniques, and note taking techniques. In this analysis, the author analyzes the phrases in four historical narrative texts entitled Mohammad Hatta: "Every action is for the sake of the country you love, don't betray.", Ki Hadjar Dewantara: "It's better to have nothing but be happy than to be wealthy but unhappy.”, History of the Beduk Musical Instrument in Malay Dance Accompaniment Music in Pontianak City, Typhoid Outbreaks in Cirebon during the Dutch East Indies Period. The research results obtained were the discovery of various uses of phrases totaling 35 in these texts. There are 10 noun phrases, 15 verb phrases, 8 prepositional phrases, and 2 adjective phrases.